Sistem Informasi Geografis Pemetaan Distribusi Tanaman Jagung Terhadap Produktivitas Pertanian Di Kabupaten Rembang Tahun 2020 - Ardianti Romsita; Bambang Agus Herlambang; Ahmad Khoirul Anam (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2024)
Abstract. Corn is the most important commodity crop after rice. Not only utilized as daily food, but there are many other uses. Rembang Regency is one of the corn producing areas in Central Java. However, the productivity of maize farming in this district is low. Many factors underlie why the productivity of maize crops is low. This study aims to examine the relationship between maize distribution and productivity. Mapping is done by utilizing Geographic Information Systems. Using Geographic Information Systems can help understand the relationship and cause and effect of the distribution of crops on the low productivity of corn in Rembang Regency. Keywords: Maize, Geographic Information System, Rembang Regency